A new index predicts early allograft dysfunction following living donor liver transplantation: A propensity score analysis. Issue 11 (November 2017) - Song, Jiu-Lin; Yang, Jian; Yan, Lu-Nan; Yang, Jia-Yin; Wen, Tian-Fu; Li, Bo; Zeng, Yong; Wu, Hong; Wang, Wen-Tao; Xu, Ming-Qing; Chen, Zhe-Yu; Wei, Yong-Gang; et al.
Abstract: Objective/Aim: The aim of this study was to identify a new index to predict early allograft dysfunction following living donor liver transplantation. Methods: The study enrolled 260 adult living donor liver transplantation recipients. Postoperative laboratory variables were assessed for their association with the prevalence of early allograft dysfunction using the inverse probability of treatment weighting and propensity-score matching (n = 93 pairs) analysis. Results: Forty-seven recipients (18.1%) developed early allograft dysfunction. In multivariable analysis, the alanine aminotransferase and gamma-glutamyl transpeptidase levels on postoperative day 1 were independent predictors of early allograft dysfunction. The alanine aminotransferase to gamma-glutamyl transpeptidase ratio (AGR) was developed. All cases were divided into two groups (Group 1 [AGR ≥ 8.47, n = 103] and Group 2 [AGR < 8.47, n = 157]). AGR ≥ 8.47 (OR 10.345, 95%CI 4.502–23.772, p <  0.001), hepatorenal syndrome (OR 3.016, 95%CI 1.119–8.125, p  = 0.029), and graft to recipient weight ratio <0.8% (OR 2.155, 95%CI 1.004–4.624, p  = 0.049) were independent risk factors for early allograft dysfunction. The prevalence of early allograft dysfunction was higher in group 1 (after adjusting for inverse probability of treatment weighting [n = 39; 37.9% vs n = 8; 5.1%] and propensity-score matching [n = 33; 35.5% vs n = 2; 2.2%]) than that in group 2 ( p <  0.001). Conclusions: The postoperative AGR is a practical index for predicting early allograft dysfunction after living donor liver transplantation.